Zakat Classification with Naïve Bayes Method in BAZNAS - Yuslena Sari; Muhammad Alkaff; Eka Setya Wijaya; Gusti Nizar Syafi'i (TECHNO: JURNAL PENELITIAN, 2021)
The National Amil Zakat Agency (BAZNAS) of the Banjar Regency, is the regional Zakat Management Agency of the Banjar Regency. BAZNAS Banjar Regency distributes the required alms according to the target to mustahik that is under the criteria or following the provisions of the Shari'a. However, BAZNAS often experiences difficulties in determining mustahik (people who are entitled to receive zakat) due to limited distribution funds and excessive data on Fakir and miskin people who are the main priority. The existence of a system that can determine two groups of recipients of the Fakir and miskin zakat based on data from the underprivileged population can help the distribution of zakat to these 2 groups. In this case, using the Naive Bayes method is very suitable in the classification of the BAZNAS mustahik determination so that it can be used to determine the prospective recipient of zakat. Based on the results of tests conducted on the Naïve Bayes classification with the Confusion Matrix calculation, the accuracy value reached 92.30%.